Nuclear Magnetic Resonance Studies of Chemical Exchange in Solution and Simulation of Chemical Exchange in Rotating Solids - Hazendonk, Paul (My University, 2000)
The primary objective of the following work is to advance the study of dynamic processes in molecules by Nuclear Magnetic Resonance. Rate measurements by NMR give rise to activation parameters of unprecedented accuracy. We have had much success with small molecules in solution phase and would like to extend these methods to larger molecules and to the solid phase.
Two studies into small molecules found: substantial entropies of activation for furfural in a series of solvents and that measured substituent effects on amide barriers could not be explained simply by Atoms in Molecules methodologies. Exchange rates measurements were made on two large sample systems: DADS which has five observable conformations, and TRH is proline-containing tripeptide with two conformations. Complete lineshape analysis and selective inversion experiments provided for reliable activation parameters.
Currently lineshape simulation methods for exchanging mUltispin systems undergoing magic-angle spinning using full theory are not available. Using the timeindependent Floquet approach it was possible to do such simulations. Since this method involves large matrices an efficient numerical method was developed. A sparse implementation of a stable formulation of the dual Lanczos algorithm made these simulations possible on a realistic time scale. The CPMAS spectra of doubly-¹³Clabelled dimethylsulfone were successfully simulated for a series of temperatures and rotor speeds.
Keywords: Chemistry; Chemistry